(untitled) (Research, Society and Development, 2022)
The informations about methodologies for evaluating the vigor of vegetable seeds is less studied, including species of less commercial interest, such as the most diverse species of pumpkins. Studies involving the storage of these seeds and the effects of chemical treatment on their vigor are necessary for a better understanding of the maintenance of the quality of pumpkin seeds. The objective of this work was to evaluate the quality of “Pumpkin of Pig” seeds under different periods of storage and chemical treatment. The experiment was carried out in the seed analysis laboratory of Instituto Federal Goiano - Campus Ceres. The treatments were: with and without chemical treatment and five storage periods (0, 30, 60, 90 and 120 days). The following analyzes were carried out: physical purity, mass of a thousand seeds, moisture content, electrical conductivity, germination, dry mass of germinated seedlings, field emergence and emergence speed index. Data were submitted to Tukey’s test (5%) by Sisvar and regression analysis. It was observed that the stored seeds lost moisture and had an increase in electrical conductivity as a function of storage. There was no significant difference in seed germination with or without the application of chemical treatment in the studied periods. The emergence of seedlings with seed treatment was higher up to 90 days.